2020
DOI: 10.1177/2048872619900090
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility of venoarterial extracorporeal membrane oxygenation in cardiogenic shock and cardiac arrest

Abstract: Background: The use of venoarterial extracorporeal membrane oxygenation in cardiogenic shock keeps increasing, but its cost-utility is unknown. Methods: We studied retrospectively the cost-utility of venoarterial extracorporeal membrane oxygenation in a five-year cohort of consequent patients treated due to refractory cardiogenic shock or cardiac arrest in a transplant centre in 2013–2017. In our centre, venoarterial extracorporeal membrane oxygenation is considered for all cardiogenic shock patients potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 36 publications
1
29
1
Order By: Relevance
“…The study by Kawashima et al reported on costs according to first documented rhythm in ECPR patients [ 11 ], with median costs of US$22,305 in asystole/pulseless electrical activity (PEA) patients and US$30,553 in patients presenting with ventricle tachycardia/ventricle fibrillation (VT/VF). The study by Jäämaa-Holmberg et al provided a median cost of US$187,282 [ 13 ], and for the non-US studies, the costs ranged between a mean of US$851 and US$4615. Jäämaa-Holmberg provided a median cost of US$5852 per day in hospital [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study by Kawashima et al reported on costs according to first documented rhythm in ECPR patients [ 11 ], with median costs of US$22,305 in asystole/pulseless electrical activity (PEA) patients and US$30,553 in patients presenting with ventricle tachycardia/ventricle fibrillation (VT/VF). The study by Jäämaa-Holmberg et al provided a median cost of US$187,282 [ 13 ], and for the non-US studies, the costs ranged between a mean of US$851 and US$4615. Jäämaa-Holmberg provided a median cost of US$5852 per day in hospital [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study by Jäämaa-Holmberg et al provided a median cost of US$187,282 [ 13 ], and for the non-US studies, the costs ranged between a mean of US$851 and US$4615. Jäämaa-Holmberg provided a median cost of US$5852 per day in hospital [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations